ChemInform Abstract: Asymmetric Organocatalytic Michael—Hemiacetalization Reaction: Access to Chiral Spiro cis‐δ‐Lactones by in situ Oxidation of Spiro δ‐Lactols. Issue 34 (1st August 2013) - Wei, Mo‐Hui; Zhou, Yi‐Rong; Gu, Liang‐Hu; Luo, Fan; Zhang, Fang‐Lin
Abstract The 1‐nitromethylcycloalkanols (I) and (VI) react with α, β‐unsaturated aldehydes to give spiro cis‐δ‐lactol intermediates.